2019
DOI: 10.1063/1.5083682
|View full text |Cite
|
Sign up to set email alerts
|

Complexity surrounding an apparently simple Fermi resonance in p-fluorotoluene revealed using two-dimensional laser-induced fluorescence (2D-LIF) spectroscopy

Abstract: Two-dimensional laser-induced fluorescence (2D-LIF) spectroscopy is a powerful tool allowing overlapped features in an electronic spectrum to be separated, and interactions between vibrations and torsions to be identified. Here the technique is employed to assign the 790-825 cm -1 region above the origin of the S1  S0 transition in para-fluorotoluene (pFT), which provides insight into the unusual time-resolved results of Davies and Reid [Phys. Rev. Lett. 109, 193004 (2012)]. The region is dominated by a pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…26) and those at ~800 cm -1 (Ref. 27) using 2D-LIF, and compared the results to our earlier ZEKE work. 18,21,23 The assignments of the 2D-LIF spectra indicated that both vibrational interactions and vibration-torsional coupling were occurring.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…26) and those at ~800 cm -1 (Ref. 27) using 2D-LIF, and compared the results to our earlier ZEKE work. 18,21,23 The assignments of the 2D-LIF spectra indicated that both vibrational interactions and vibration-torsional coupling were occurring.…”
Section: Introductionmentioning
confidence: 87%
“…As well as 111 (see Figure 5), there are also other emissions, with those in the range ~840-855 cm -1 being assigned as 142, 91 and 292. (Note that there was some indication that, as well as 9 1 and 29 2 being in Fermi resonance in the S1 state, 27,47 the 91 and 292 levels may be in Fermi resonance in S0, and the same was true of + 9 1 and + 29 2 in D0 + . 27 )…”
Section: Assignmentsmentioning
confidence: 96%
See 3 more Smart Citations